Student performance classification: data, features and classifiers / Muhammad Hareez Mohd Zaki ... [et al.] - Mohd Zaki, Muhammad Hareez; Abdul Aziz, Mohd Azri; Sulaiman, Suhana; Hambali, Najidah (UiTM Press, 2023)
Recognising student’s performances are one of the factors that contribute to the Educational Data Mining (EDM) which make it important in determining the students-related factors that affect their performance. Thus, a review on the student performance classification based on its data, features and classifiers has been made. The purpose of the study is to review on classification of student performance, data and features that are used in analysing student performance and also the classifiers that are used in classifying the performances of the student. By reviewing these factors, the insight of the data and features used during classification of student performance can be obtained. There are also many different types of classifiers that were used in student performance classification. A few classifiers had been reviewed to gain understanding in their performance towards the data classification of students’ performance.